THE EFFECT OF USING SONGS ON YOUNG LEARNERS AND THEIR MOTIVATION FOR LEARNING ENGLISH (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2021)
Songs are appreciated for their linguistic, pedagogical, cultural and entertaining features and those areprecious language learning materials. They can be used to teach and develop every aspect of a language. This paper aims to verify these claims and confirm the effectiveness of using songs as a means to improve young learners’ English language vocabulary and to determine whether songs influence young learners’ motivation to learn English.